Muscle Gene Therapy - Duan, Dongsheng (Springer New York : Imprint: Springer, 2010)
Muscle disease represents an important health threat to the general population. For thousands of years, a cure has been deemed extremely remote, if not impossible, for many relentless muscle diseases such as Duchenne muscular dystrophy. The cloning of muscle disease genes and the prospect of introducing the normal gene to diseased muscle by gene therapy finally bring the hope of a cure. Tremendous progress has been made chasing the muscle gene therapy dream over the past two decades. Valuable information is scattered in the literature. This book represents the first compilation specifically dedicated to issues related to muscle gene therapy. It offers a much needed, up-to-date overview and perspective on the current strategies and status of muscle gene therapy. It covers the cutting edge development of a variety of fascinating strategies such as exon-skipping, AAV gene therapy, RNAi and stem cell approaches. With contributions from prominent investigators in the field, it provides a framework to translate bench science to clinical practice in the upcoming years. This book is a must-have for anyone who is interested in muscle gene therapy including established investigators, clinicians, post-doctoral fellows, graduate students, funding agencies, patients and their families and friends.